FUTURE TEACHERS AS CREATORS OF INTELLECTUAL CAPITAL OF THE NEW UZBEKISTAN - Adilova Tursunoy Kadirovna (Ecominds Press, 2025)
This article highlights the importance of future teachers as key agents of intellectual renewal in the context of national reforms and global challenges. The focus is placed on teachers as carriers and transmitters of human capital, shaping the country’s intellectual resources. The necessity of changing the paradigm of teacher training is substantiated, foreign experiences and the challenges of the digital era are analyzed, and practical ways to enhance the role of teachers in the education system of New Uzbekistan are proposed.
Keywords: Intellectual capital, teacher of the future, educational reforms, competency-based approach, human resources, educational policy, sustainable development.